Control of invasive meningococcal disease: is it achievable? - Marshall, H; Wang, B; Wesselingh, S; Snape, M; Pollard, A (Lippincott, Williams and Wilkins, 2016)
Neisseria meningitidis still leads to deaths and severe disability in children, adolescents and adults. Six different capsular groups of N. meningitidis cause invasive meningococcal disease in the form of meningitis and septicaemia in humans. Although conjugate meningococcal vaccines have been developed to provide protection against four of the capsular groups causing most diseases in humans, vaccines against capsular group B, which causes 85% of cases in Australia and the United Kingdom, have only recently been developed. A capsular group B meningococcal vaccine – 4CMenB (Bexsero) – has recently been licensed in the European Union, Canada and Australia. In Australia, a submission for inclusion of 4CMenB in the funded national immunization programme has recently been rejected. The vaccine will now be introduced into the national immunization programme in the United Kingdom following negotiation of a cost-effective price. With the current low incidence of invasive meningococcal disease in many regions, cost-effectiveness of a new capsular group B meningococcal vaccine is borderline in both the United Kingdom and Australia. Cost-effectiveness of an infant programme is determined largely by the direct protection of those vaccinated and is driven by the higher rate of disease in this age group. However, for an adolescent programme to be cost-effective, it must provide both long-term protection against both disease and carriage. The potential of vaccination to reduce the rate of severe invasive disease is a real possibility. A dual approach using both an infant and adolescent immunization programme to provide direct protection to those age groups at highest risk of meningococcal disease and to optimize the potential herd immunity effects is likely to be the most effective means of reducing invasive meningococcal disease. This commentary aims to describe the known disease burden and consequences of meningococcal disease, and the development and potential effectiveness of new capsular group B meningococcal vaccines.